2004
DOI: 10.1103/physreve.70.041801
|View full text |Cite
|
Sign up to set email alerts
|

Entanglements in quiescent and sheared polymer melts

Abstract: We visualize entanglements in polymer melts using molecular dynamics simulation. A bead at an entanglement interacts persistently for long times with the non-bonded beads (those excluding the adjacent ones in the same chain). The interaction energy of each bead with the non-bonded beads is averaged over a time interval τ much longer than microscopic times but shorter than the onset time of tube constraints τe. Entanglements can then be detected as hot spots consisting of several beads with relatively large val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Since the relation between the contacts among chains in Kremer-Grest simulations and the entanglement used in the entanglement-based models (such as our model) has not been clarified, our slipspring reconstruction rules can not be related to the dynamics in Kremer-Grest simulations at this time being. For instance, it has been reported that in Kremer-Grest simulations the long-lived contacts between two chains are constructed not only around the chain ends but also interior of the chain [58,59]. But in the presented model (and the other entanglement-based models) assumes that the entanglement reconstruction occurs only at the chain ends.…”
Section: Comparison With Earlier Modelsmentioning
confidence: 96%
“…Since the relation between the contacts among chains in Kremer-Grest simulations and the entanglement used in the entanglement-based models (such as our model) has not been clarified, our slipspring reconstruction rules can not be related to the dynamics in Kremer-Grest simulations at this time being. For instance, it has been reported that in Kremer-Grest simulations the long-lived contacts between two chains are constructed not only around the chain ends but also interior of the chain [58,59]. But in the presented model (and the other entanglement-based models) assumes that the entanglement reconstruction occurs only at the chain ends.…”
Section: Comparison With Earlier Modelsmentioning
confidence: 96%
“…In this direction, several attempts have been made. Assuming that entanglements lead to persistent chain interactions, the detection of long-lived chain contacts [48][49][50][51] was the target of many simulations. Although it was found that such contacts do exist, it is rather difficult to evolve this picture further.…”
Section: Introductionmentioning
confidence: 99%
“…According to Refs. [7][8][9] some effects should be expected when the shear rate approaches or exceeds the inverse of the slower relaxation time, in our case s nm . According the Cox-Merz rule steady-shear-viscosity versus shear-rate curve has the same shape and values as the complex-viscosity (obtained through oscillatory shear) versus frequency curve for comparable rate and frequency, i.e., for _ cðs À1 Þ ¼ xðrad=sÞ : gð_ cÞ ¼ jg à ðxÞj _ c¼x .…”
Section: Dynamics Of a Polymeric Melt Under Shear In The Nonlinear Rementioning
confidence: 97%
“…Recent works, both experiments [7,8] and computer simulations [9], showed that the application to polymeric systems of a shear flow at enough high rates, usually closer to the longer relaxation time, produces an acceleration of such relaxation [8], a decrease of the viscosity (shear thinning) observed at those rates, or, at least a mild reduction of the dielectric intensity related to such relaxation process [7]. In this regime of fast flow, obtained by applying large amplitude oscillatory shear, the amplitude of the viscoelastic response is not anymore directly proportional to the amplitude of the imposed deformation and so the non-linear regime is attained.…”
Section: Dynamics Of a Polymeric Melt Under Shear In The Nonlinear Rementioning
confidence: 99%
See 1 more Smart Citation